Challenges in spectroscopy: accuracy versus interpretation from isolated molecules to condensed phases. Issue 7 (1st February 2019) - Puzzarini, Cristina; de Lara-Castells, Maria Pilar; Ramos, Maria J.
Abstract : This themed issue includes a collection of articles on Challenges in spectroscopy: accuracy versus interpretation from isolated molecules to condensed phases.